Identification of colletotrichum species causing anthracnose on tahiti lime, tree tomato and mango (2009)
In Colombia, citrus, tree tomato and mango crops are likely to suffer considerable losses from anthracnose caused by several Colletotrichum species, which were identified by the present study on infected organs of the three fruit crops, sampled in different regions of the country. Identification was based on their morphological and molecular characteristics, as well as on fungicide (benomyl and copper hydroxide) sensitivity and pathogenicity tests. The latter assessed infectivity on both the original hosting crop and the other two crops (crossed infection), by putting the fungi in contact with organs taken from the three fruit crops. Molecular identification of the Colletotrichum species was carried out through amplification of rDNA ITS regions by means of C. gloeosporioides (CgInt) and C. acutatum (CaInt2) specific primer PCR combining the use of ITS4 universal primer. The results indicate that C. acutatum is the infectious agent in Tahiti lime and tree tomato, and so is C. gloeosporioides in mango. Although C. acutatum is the infectious agent in two diferent fruit species, the strains proved to be specific of their original hosts.